The interaction of parsing rules and argument – Predicate constructions: implications for the structure of the Grammaticon in FunGramKB - María del Carmen Fumero Pérez; Ana Díaz Galán (Revista de Lingüística y Lenguas Aplicadas)
The Functional Grammar Knowledge Base (FunGramKB), (Periñán-Pascual and Arcas-Túnez 2010) is a multipurpose lexico-conceptual knowledge base designed to be used in different Natural Language Processing (NLP) tasks. It is complemented with the ARTEMIS (Automatically Representing Text Meaning via an Interlingua–based System) application, a parsing device linguistically grounded on Role and Reference Grammar (RRG) that transduces natural language fragments into their corresponding grammatical and semantic structures. This paper unveils the different phases involved in its parsing routine, paying special attention to the treatment of argumental constructions. As an illustrative case, we will follow all the steps necessary to effectively parse a For-Benefactive structure within ARTEMIS. This methodology will reveal the necessity to distinguish between Kernel constructs and L1-constructions, since the latter involve a modification of the lexical template of the verb. Our definition of L1-constructions leads to the reorganization of the catalogue of FunGramKB L1-constructions, formerly based on Levin’s (1993) alternations. Accordingly, a rearrangement of the internal configuration of the L1-Constructicon within the Grammaticon is proposed.